'Academese', 'church chat' and the fear of alienating the congregation: Exploring church preaching as a lexical environment. Issue 1 (5th July 2018) - Malmström, Hans
Abstract : This study is concerned with communication in religious settings, with a specific focus on the professional practice of preaching. The paper addresses concerns raised within preaching research that preaching in mainline denominations is too academic and/ or draws too heavily on theological jargon; however, little empirical evidence for this has been presented. To learn more about preachers' communicative engagement with their congregations in this regard, the study focuses on preaching vocabulary in three denominations (the Church of England, the Baptist Union of Great Britain and the Catholic Church for England and Wales), using the concept of lexical environment to profile 150 contemporary sermons given in England in the UK and drawing on interviews with practising preachers. Findings indicate (1) that preaching makes only limited use of academic and potentially difficult religious vocabulary, and (2) that preaching is an inclusive, sensitive and carefully attuned lexical environment where preachers' lexical practices appear to help them achieve their discursive aims. The study furthermore shows how preachers are lexically aware and engage actively with vocabulary at various stages of sermon preparation. In addition, this study goes some way to show how applied approaches to linguistics can be of service to homiletics.